Biology education student responses on teaching campus program - Hafizatil Adni; A. Wahab Jufri; Karnan Karnan (Jurnal Pijar Mipa, 2023)
The teaching campus (kampus mengajar) is part of the Independent Learning Independent Campus (Merdeka Belajar Kampus Merdeka), MBKM program which provides opportunities for students to provide teaching assistance in basic education units. This study aims to analyze the responses of Biology Education Study Program students at FKIP, University of Mataram to the teaching campus. This study uses a quantitative descriptive method, with sample in this study were 57 students participating in campus teaching batches 2, 3, 4, and 5. The results showed that students’ responses to the teaching campus from agree to disagree were obtained with 37.65% positive responses, 29.82% neutral responses and 33.3% negative responses. Student responses in indicators of knowledge about the teaching campus (42.11%) were positive, (29.82%) neutral, (17.54%) negative, and (10.53%) very negative. Student responses to the teaching campus activity indicator (33.33%) were positive, (36.84%) neutral, (24.56%) negative, and (5.26%) very negative. Student responses to the benefits of the teaching campus indicators (10.53%) were very positive, (19.30%) positive, (47.37%) neutral, (17.54%) negative, and (5.26%) very negative. This shows that most students respond positively to the teaching campus program, because through the teaching campus students get teaching experience, understand the context related to education, and can develop soft skills by doing activities directly in the community and developing creativity to make new innovations to create independent learning.